Pseudoanaplectinia yumotoi, A New Ovoviviparous Myrmecophilous Cockroach Genus and Species from Sarawak (Blattaria: Blattellidae; Blattellinae) - Louis M. Roth (Psyche: A Journal of Entomology)
Pseudoanaplectinia yumotoi, a new myrmecophilous cockroach genus and species, is described from Sarawak. Based on the male genital phallomeres, it is placed in the Blattellidae: Blattellinae. The genus is ovoviviparous and probably arose from an anaplectinoid-like ancestor. This is the third case of ovoviviparity arising in the Blattellidae. The cockroach has a symbiotic relationship with an ant Crematogaster sp.